The Impact of Social Media Marketing, Consumptive Behaviour, and Financial Self-Control on the Financial Well-being of Students in Medan City - Tanjung, Ahmad Albar; Nurhayati; Muliyani (Jurnal Manajemen, 2026)
University students represent the younger generation who will become the pillars of national development in the future. Financial well-being is a crucial aspect of student development, reflecting their ability to manage finances responsibly and prepare for long-term financial stability. This study aims to analysed the influence of social media marketing, consumptive behaviour, and financial self-control on the financial well-being of university students in Medan, Indonesia. Utilizing a quantitative research design, Sampling in this study was conducted using purposive sampling. primary data were collected through questionnaires distributed to 100 students from various universities in Medan. Data analysis was conducted using the Structural Equation Modelling Partial Least Squares (SEM-PLS) method with the Smart-PLS application. The results show that social media marketing has a negative and significant effect on financial well-being, as does consumptive behaviour. In contrast, financial self-control has a positive and significant impact on financial well-being. These findings highlight the essential role of financial self-control in promoting student financial well-being and reducing the negative effects of social media marketing and consumptive tendencies.